Correlating drug–target kinetics and in vivo pharmacodynamics: long residence time inhibitors of the FabI enoyl-ACP reductase. Issue 9 (6th June 2016) - Daryaee, Fereidoon; Chang, Andrew; Schiebel, Johannes; Lu, Yang; Zhang, Zhuo; Kapilashrami, Kanishk; Walker, Stephen G.; Kisker, Caroline; Sotriffer, Christoph A.; Fisher, Stewart L.; Tonge, Peter J.
Abstract : A mechanistic PK/PD model that enables predictions of in vivo drug activity and an assessment of target vulnerability. Abstract : Drug–target kinetics enable time-dependent changes in target engagement to be quantified as a function of drug concentration. When coupled to drug pharmacokinetics (PK), drug–target kinetics can thus be used to predict in vivo pharmacodynamics (PD). Previously we described a mechanistic PK/PD model that successfully predicted the antibacterial activity of an LpxC inhibitor in a model of Pseudomonas aeruginosa infection. In the present work we demonstrate that the same approach can be used to predict the in vivo activity of an enoyl-ACP reductase (FabI) inhibitor in a model of methicillin-resistant Staphylococcus aureus (MRSA) infection. This is significant because the LpxC inhibitors are cidal, whereas the FabI inhibitors are static. In addition P. aeruginosa is a Gram-negative organism whereas MRSA is Gram-positive. Thus this study supports the general applicability of our modeling approach across antibacterial space.